(Electronics and Photonics Division Award Address) Performance of InGaN/GaN-Based Light Emitting Diodes Fabricated with ZnO Nanorods. (9th April 2018) - Kim, Ki Seok; Song, Sungjoo; Seong, Tae-Yeon
Abstract : In this study, ITO/ZnO nanorod electrodes were used to enhance the light extraction efficiency (LEE) of InGaN-based LEDs. The ZnO nanorods were grown on ITO using a simple non-catalytic polymer-template wet-chemical growth method at a temperature of 90 ºC. In0.14 Ga0.86 N/GaN-based LEDs (λ = 453 nm) were fabricated with well-aligned ZnO nanorods (WAZNR), not-aligned ZnO nanorods (NAZNR), and bare-ITO electrodes (reference), and their electrical and optical properties were characterized. LEDs with WAZNR showed 39.9% and 25.4% higher electroluminescence intensity than those with bare-ITO and NAZNR, respectively. The LED fabricated with WAZNR exhibited 44.4% and 30.2% higher light output power at 100 mA, respectively, than those with ITO-only and NAZNR. Furthermore, the external quantum efficiency (EQE) at 100 mA of the LED with WAZNR was 37.1% and 43.1% higher than those of the LEDs with bare-ITO and NAZNR, respectively.